Expansion of pathogen-specific mono- and multifunctional Th1 and Th17 cells in multi-focal tuberculous lymphadenitis. - Nathella Pavan Kumar; Rathinam Sridhar; Vaithilingam V Banurekha; Dina Nair; Mohideen S Jawahar; Thomas B Nutman; Subash Babu (PLoS ONE, 2013)
Th1 and Th17 responses are known to play an important role in immunity to pulmonary tuberculosis (PTB), although little is known about their role in extrapulmonary forms of tuberculosis (TB).To identify the role of Th1, Th17, and Th22 cells in multi-focal TB lymphadenitis (TBL), we examined mycobacteria-specific immune responses in the whole blood of individuals with PTB (n = 20) and compared them with those with TBL (n = 25).Elevated frequencies of CD4(+) T cells expressing IFN- γ, TNF-α, and IL-2 were present in individuals with TBL compared with those with PTB at baseline and in response to ESAT-6 and CFP-10. Similarly, increased frequencies of CD4(+) T cells expressing IL-17A, IL-17F, and IFN-γ were also present in individuals with TBL at baseline and following ESAT-6 and CFP-10 stimulation although no significant difference in frequency of Th22 cells was observed. Finally, frequencies of Th1 (but not Th17) cells exhibited a significantly negative correlation with natural regulatory T cell frequencies at baseline.Multi-focal TB lymphadenitis is therefore characterized by elevated frequencies of Th1 and Th17 cells, indicating that Th1 and Th17 responses in TB disease are probably correlates of disease severity rather than of protective immunity.